Strategi Pengelolaan Akun Instagram @Reyogchestra dalam Mempromosikan Budaya Reog Ponorogo - Rifa'i Riski Isha Mahendra; Nieldya Nofandrila (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Reog Ponorogo is one of Indonesia’s traditional performing arts originating from Ponorogo Regency, East Java, which continues to thrive and attract appreciation from both artists and the general public across various regions. This study aims to analyze the cultural communication strategy implemented by the Instagram account @Reyogchestra in promoting Reog Ponorogo in the digital era, focusing on how social media is utilized as a medium for cultural preservation among younger generations. This research employs a qualitative method with a constructivist paradigm, while data analysis follows the interactive model of Miles and Huberman. The SOME Model (Share, Optimize, Manage, Engage) serves as the main analytical framework to examine the applied digital strategy, complemented by the Participatory Communication Theory to understand audience engagement and the role of social media in cultural preservation. Data were collected through in-depth interviews, observation, and documentation of the account’s digital activities. The findings reveal that @Reyogchestra consistently applies a community-based digital communication strategy that is participatory, adaptive, and sustainable, effectively expanding audience reach while strengthening efforts to preserve the cultural heritage of Reog Ponorogo in the digital sphere.